ANALYSIS OF FACTORS INFLUENCING ACCOUNTING STUDENTS' PERCEPTION OF STUDENT INTEREST IN BECOME PUBLIC ACCOUNTANTS - Fifitri Ali; Karina Syafzah (Realible Accounting Journal, 2023)
This study aims to determine the effect of social values, family demands, financial rewards, gender and work environment on students' interest in becoming public accountants. The objects of this research are accounting students majoring in D3 Politeknik Caltex Riau (PCR) and accounting students at Universitas Lancang Kuning (UNILAK). The sampling technique in this study used a random sampling technique because this technique is considered more efficient so that it does not make it difficult for researchers to obtain data. The number of samples using the Slovin formula was 186 people. the allocation of the distribution of the number of samples is taken proportionally based on the number of each student majoring in accounting at the two campuses. The data collection method is a survey method by distributing questionnaires. The results of this study indicate that the variables of social values, financial rewards, and work environment have a positive and significant influence on students' interest in becoming public accountants. While the variables of family demands and gender have no effect.